Cover Image. Issue 3 (29th May 2021) - Hayano, Junichiro; Ueda, Norihiro; Kisohara, Masaya; Yuda, Emi; Watanabe, Eiichi; Carney, Robert M.; Blumenthal, James A.
Abstract : The cover image is based on the Original Article Risk stratification after acute myocardial infarction by amplitude‐frequency mapping of cyclic variation of heart rate by Junichiro Hayano et al., https://doi.org/10.1111/anec.12825 .